Marked negative T waves in athletes: ECG normalization after detraining - Vessella, T.; Cardillo, R.; Bianco, M.; Palmieri, V.; Zeppilli, P. (The Journal of Sports Medicine and Physical Fitness, 2013)
Ventricular repolarization abnormalities (VRA) in athletes with apparently normal hearts, have always represented a challenging problem for sports physicians. We describe the case of an athlete with giant negative T waves and ST segment depression on resting electrocardiogram (ECG), "small" left ventricular cavity size and mild segmental hypertrophy at the echocardiogram (ECHO). After only 2 months of detraining, ECHO features were almost identical but ECG abnormalities disappeared. He has been followed in our Outpatient Clinic for 17 years, during which he had some cardiovascular complications, strongly suggestive of Hypertrophic Cardiomyopathy. At last stress test ECG, moreover, reappearance of VRA at high workloads and during the recovery period was documented. In conclusion, even if marked VRA disappear after a detraining period, we believe that they always represent a mark of an underlying disease and not just a sign of athlete`s heart.